THE STUDENTS' MEMORY LANGUAGE LEARNING STRATEGY IN MASTERING ENGLISH MATERIALS AT VOCATIONAL SCHOOL LEVEL - Khalifasati, Aulinadia; Susanto, Dias Andris (PRIMER : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to investigate students' perceptions of the Memory language learning strategy in mastering various English as a Foreign Language (EFL) language skills in SMK N 7 Semarang. A descriptive qualitative method was used with a questionnaire survey to collect data from 34 students of SMK N 7 Semarang who completed the nine items of the Strategy Inventory for Language Learning (SILL) questionnaire and a Background Characteristics survey. Three simultaneous actions in data analysis, according to Miles & Huberman, (1994): data reduction, data display, conclusions, and drawing/verification. The findings showed from the frequently used memory language strategy was to remember new words or phrases by remembering their location on the page on the board. The conclusions of the study's findings indicate that how English is used in practice affects how well it was learned. On the other hand, the findings showed a connection between using memory strategies and effectively learning English the most popular memory language learning strategy was remembering new words or phrases by remembering their location on the page, on the board.